HIV/AIDS infection in people aged 50 and older. Cienfuegos 1986-2021 - Leticia Castro Morejón; Lourdes Elena Duany Badell; Dianelys María López Castro; Joliette Rodríguez Peña; Vivian Isabel Chávez Pérez; Miladys Llanes Cartaya (Medisur)
Background: infection by the human immunodeficiency virus is one of the most important sexually transmitted infections for health worldwide and one of the most frightening of this century. Objective: to characterize the infection by the human immunodeficiency virus in people aged 50 years and older. Methods: a cross-sectional descriptive observational research was carried out, which included all the people diagnosed with the human immunodeficiency virus, in Cienfuegos, from 1986 to 2021. The analyzed variables were: age, sex, sexual orientation, research group, diagnoses by year and residence municipality. Results: people in the age group of 50 to 59 years contributed the highest incidence with 75.21%; the predominant sexual orientation was homosexual (58,9 %). According to the research groups, in the three age groups the captured group stands out with 41.88%. A sustained increase was observed in the province, mainly in the male sex, rising in recent years. Conclusions: the increase in patients aged 50 and older diagnosed with human immunodeficiency virus indicates that it is necessary to address the problem with a different clinical-epidemiological approach. These characteristics increase the risk of HIV infection, they must be monitored with the application of the MINSAP 50 and + Work Line. It is necessary to carry out activities aimed at reducing the risk.